Philosophical Views on the Education System in Lombok - Mulyan, Andi (JUPE : Jurnal Pendidikan Mandala, 2024)
This article discusses philosophical views on the education system in Lombok, Indonesia. By utilizing an educational philosophy approach, this research aims to explore how philosophical values and principles can influence teaching methods, curriculum and educational outcomes in the area. This research uses qualitative methods with data analysis from various sources, including interviews with educators, student surveys, and literature reviews. It is hoped that the results of this research will provide new insight into the importance of a philosophical approach in developing a better education system in Lombok.